Information literacy in the workplace : 5th European Conference, ECIL 2017, Saint Malo, France, September 18-21, 2017, revised selected papers /: 5th European Conference, ECIL 2017, Saint Malo, France, September 18-21, 2017, revised selected papers. (2018) - Unknown
No abstract available